A Missio Dei Reinterpretation of Matthew 28:19–20 and Its Implications for Children’s Faith Formation - Yanni Paembonan; Yunus D. A. Laukapitang; Kesia Kesy Justip (Didache: Journal of Christian Education, 2026)
This article aims to reinterpret the Great Commission within the framework of missio Dei, highlighting the significance of children’s faith formation as an integral aspect of the church’s mission. The primary issue addressed is the tendency to interpret the Great Commission narrowly, emphasizing verbal evangelism and individual conversion while giving limited attention to long-term character and faith development, particularly within the challenges of a digital society. The theoretical approach includes holistic missiology and linguistic analysis of the Greek text of Matthew 28:19-20, focusing on the imperative “make disciples” and its contextual understanding. The research employs a qualitative method through theological-contextual analysis and a systematic literature review, including exegetical examination of biblical texts and critical reflection on contemporary church mission practices. The findings indicate that reinterpreting the Great Commission through the missio Dei paradigm provides a broader understanding of the role of children’s faith formation within the church’s mission, particularly through collaboration among families, church communities, and modern media to nurture holistic discipleship. The novelty of this research lies in its integration of the missio Dei paradigm with children’s faith formation as a central missional focus an approach that remains underexplored in contemporary missiological studies. The conclusion emphasises the need for a paradigm shift in mission perception and practice to sustain the church’s mission in the digital age.